Early Identification of Sacroiliitis in Patients with Suspected Spondyloarthritis: A Challenging Task - Nessib, Dorra B.; Bouaziz, Mouna Chelli; Maatallah, Kaouther; Ladeb, Mohamed Fethi; Kchir, Mohamed Montacer; Riahi, Hend; Hamdi, Wafa (Current Rheumatology Reviews, 2023)
Objective: The purpose of this study was to assess the performance of computed tomography (CT) scan and magnetic resonance imaging (MRI) for detecting sacroiliitis in nonradiographic SpA (nr-SpA). Methods: This cross-sectional monocentric double-blind study included 63 patients consulting for symptoms suggestive of SpA between February 2014 and February 2017. Patients with conventional radiographs showing a confirmed sacroiliitis (grade 3 or 4) were not included. Eligible patients underwent CT and MRI of sacroiliac joints (SIJ). CT and MR images were interpreted by 2 experienced musculoskeletal radiologists blinded to clinical and laboratory data. Two professors in rheumatology blinded to radiologists’ conclusions analyzed clinical data, laboratory tests, HLA typing, X-rays, CT and MRI images, and divided the patients into 2 groups: confirmed nr-SpA or no SpA. This classification was considered the gold standard when analyzing the results. Results: 46 women and 17 men were included in this study. 47 patients were classified as confirmed nr-SpA (74.6%) and 16 patients as no SpA (25.4%). Sensitivity, specificity, and positive and negative predictive values of CT and MRI for detecting sacroiliitis were, respectively, estimated at 71.7%, 71.4%, 89.2%, 43.5%, and 51.2%, 100%, 100%, and 40%. CT and MRI findings were found to be statistically associated (p<0.001). Conclusion: SIJ MRI is a highly specific method in the detection of sacroiliitis, but with a moderate sensitivity. SIJ CT scan, usually known as the third option after radiography and MRI, has much greater diagnostic utility than it has been documented previously.
Keywords: computed tomography